Nuclear irradiation effects on additive manufactured Inconel 625 & 718 - Andurkar, Mohanish (Kansas State University, 2024)
The effects of neutron irradiation and extreme environment conditions on the structural integrity of parts additively manufactured (AM) via the laser-powder bed fusion method (L-PBF), the most common AM method for producing strong/durable metallic parts, is not currently well understood. This is hampering the direct, dependable, and immediate use of AM for generating compact/efficient, functional equipment for very small modular reactors (SMRs) and nuclear propulsion. This dissertation focuses on AM materials most suitable for operating within extreme environments, i.e., nickel-based superalloys. These alloys are currently used for nuclear applications such as control rods, tension springs, fuel channel spacers, and more, since they possess superior properties such as corrosion resistance, creep resistance, and strength at elevated temperatures. In many cases, AM enables a more cost efficient and securer means for fabricating SMR structural components by reducing the number of suppliers required for component assembly and allowing for on-site/remote fabrication. This research aims to better understand the difference in mechanical properties of L-PBF nickel-based superalloys (and wrought counterparts), before and after distinct types of neutron irradiation to accelerate their safe, reliable use in nuclear applications. The major objective is to quantify the microhardness of two nickel-based superalloys additively manufactured via L-PBF, i.e., Inconel 718 (IN718) and Inconel 625 (IN625). Another objective is to measure and compare the residual stress in L-PBF samples built at different orientations and post-processing heat treatment schedules. Effects of build orientation during L-PBF and post-AM heat treatments on radiation hardening resistance are investigated. Neutron damage mechanisms via irradiation-induced hardening will be characterized. Although neutron radiation hardening defects within conventionally machined metals are commonly reported in the literature, this research is among the first of its kind focused on L-PBF nickel-based superalloys. The findings from this research will give a better head-to-head comparison between the performance of AM and conventionally machined nickel-based superalloys under similar neutron irradiation environments. In practice, nuclear reactor components are irradiated with thermal neutrons, which have relatively low energy spectra, over several years, leading to accumulated damage and the generation of radioactive isotopes. This complicates the qualification of nuclear materials since the radioactivity level of post-service components makes inspection time consuming. Thus, alternative forms of accelerated irradiation testing such as fast neutron irradiation are investigated herein. Fast neutron irradiation produces lower levels of radioactivity in metals while still providing relevant damage levels on specimens. Key results indicate that after full spectrum neutron irradiation, most L-PBF samples showed a higher tolerance towards radiation-induced hardening relative to the wrought samples. After fast neutron irradiation, IN625 and IN718 samples demonstrated hardening at the beginning of exposure, but later underwent radiation softening, most likely due to dislocation dissolution in the microstructure. L-PBF build orientation and post-processing heat treatment was also found to play a vital role in the amount of residual stress formed in IN625. Heat treatment at higher temperature reduces detrimental surface tensile residual stresses. All these precious experimental data demonstrate a noteworthy structural integrity of L-PBF materials after their exposure to different irradiation environments. Results provide insight into how one may minimize radiation hardening defects in such materials for maintaining material property constraints for a targeted service life. Research findings should assist engineers in selecting and interpreting an appropriate heat treatment for L-PBF nickel-based superalloys for increased radiation damage resistance. Major results can increase confidence levels for adopting AM for building nuclear reactor components which perform the same or better than conventionally manufactured components.
Keywords: Laser powder bed fusion; Radiation damage; Microstructure; Residual stress3D printing